Importance Du Couplage De L’inventaire Des Plantes Mellifères Et De L’analyse Pollinique Des Miels De La Saison Des Pluies En Zone Ouest Soudanienne Au Nord-Bénin - Sfich T. B. Ahouandjinou; Monique G. Tossou; Hounnankpon Yédomonhan; Adéline Zanou; Aristide C. Adomou; Akpovi Akoègninou; Comlan M. Koudegnan (European Scientific Journal, ESJ, 2017)
The melliferous plants vary from one area to another according to biotic, climatic and ecological factors. This study was realized in the Sudanese region of Benin, in order to inventorize honey plants visited by the honeybee Apis mellifera adansonii Latreille. Pollen analysis of 34 samples of honey from three apiaries in the northwest of the country, combined with direct observations around each apiary within 1000 m radius were realized per month. In total 129 species were censised including 109 species inventorized on the field and 73 taxa identified through pollen analysis. Among these taxa, 43 are identified until species level. The contribution of pollen analysis to the knowledge of melliferous plants is 15.50%. The pollen analysis of honeys and visual inventory of honey plants field are two complementary methods of studying the honey flora.